PENGARUH KUALITAS PRODUK, KUALITAS PELAYANAN DAN HARGA TERHADAP KEPUASAN KONSUMEN PADA AYAM GEPREK MBAK MIMIN DI JANGKAR DENGAN KEPUTUSAN PEMBELIAN SEBAGAI VARIABEL INTERVENING - Ismayani, Meiriyanti; Arief, Mohammad Yahya; Praja, Yudha (Fakultas Ekonomi dan Bisnis, 2024)
Dapur Mimin is a small and medium-sized enterprise (SME) operating in the culinary sector, with its signature dish being Ayam Geprek Mbak Mimin. However, sales data over the past five months have shown a decline due to intense market competition and less effective marketing strategies. This study focuses on the customers of Ayam Geprek at Dapur Mimin, located in the Arjasa sub-district. The population of this study consists of Dapur Mimin’s customers, and the sampling technique used is purposive sampling. Data analysis and hypothesis testing in this study are conducted using Structural Equation Modeling - Partial Least Square (PLS-SEM). The results of hypothesis testing for direct effects using the Smart PLS 3.0 application show that product quality has a significant positive effect on purchase decisions, service quality has a negative but not significant effect on purchase decisions, and price has a significant positive effect on purchase decisions. Furthermore, product quality has a significant positive effect on customer satisfaction, service quality has a significant positive effect on customer satisfaction, and price has a positive but not significant effect on customer satisfaction. Additionally, purchase decisions have a significant positive effect on customer satisfaction. The test results also indicate that product quality, service quality, and price each have a significant positive effect on customer satisfaction through purchase decisions.